Different clinical spectrum of leptospirosis - Aygün, Fatma Deniz; Avar-Aydın, Pınar Özge; Çokuğraş, Haluk; Camcıoğlu, Yıldız (The Turkish Journal of Pediatrics, 2016)
Leptospirosis is a prevalent zoonotic disease. Human infection usually occurs through exposure to environmental sources. Clinical course of leptospirosis is variable. We presented five patients, aged between 4-14 years, having a history of contact with rodents and symptoms 7-10 days after contact. The first three cases were relatives and had contact with dead rats after applying insecticides to bakery across from their house. The first case diagnosed as isolated meningitis, others as flu-like illness. The fourth case had a contact history with a rat inundate in the canalization and diagnosed as acute hepatitis. The last case, living in a village with poor sanitation, developed secondary hemophagocytic syndrome. ELISA was performed for diagnosis. High dose penicillin and additional immunosuppressive drugs for the last case were used. All cases showed recovery within 10 days. Leptospirosis should be considered in any patient presenting with an abrupt onset or prolonged fever, myalgia, headache and jaundice.